Konvergensi Pendapatan per kapita di Provinsi Kalimantan Barat dan Kalimantan Timur Tahun 2001-2007 serta Faktor-Faktor yang Mempengaruhi - Kumiawati, Sri; Suratman, Eddy (Jurnal Ekonomi dan Pembangunan Indonesia, 2009)
This research is aimed to identify disparity of per capita income in of the Kasaba border area (Kalimantan-Sarawak-Sabah) in West Kalimantan and East Kalimantan over the period 2001-2007. It was done by observing the coefficient variation that shows whether the sigma convergence happened or not. The other aims are to examine the determinant of beta convergence using OLS regressions with panel data. The results show that sigma convergence was not happened in West Kalimantan and East Kalimantan over the period 2001-2007. This indicated that the disparity of per capita income was happened. Beta convergence analysis indicated that absolute convergence was happened with convergence rate is 4.46 percent per year and the half-life convergence is 15.45 years. Development expenditure variable, work force participation rate and educational attainment were gave positive influence. On the other hand population growth variable was gave negative influence to the conditional convergence with convergence rate is 4.39 percent per year and the half-life convergence is15.71 years.